Impact resistance of sisal fiber reinforced concrete - Y K, Sabapathy; Sajeevan, Ramya; J, Rekha; V, Vishal; S, Sabarish; D, Revathy (International Journal of Engineering and Technology, 2018)
Concrete is typically a brittle material which is prone to damage when subjected to heavy impact loads. To overcome this weakness, concrete is reinforced with fibers as fibers are effective in withstanding heavy impact loads. The main objective of this experimental investigation is to study the influence of sisal fibers in concrete under impact load. The impact specimens are prepared using three grades of concrete- M20, M30 and M40 with five varying percentage of fibers- 0%, 0.5%, 1%, 1.5% and 2%. The mix designs of the respective grades of concrete are made as per the Indian standards. The specimens after curing for 28 days were subjected to impact loads using the standard drop weight impact machine confining to ASTM standards. Also cube and cylinder specimens are prepared and tested to ascertain the compressive and tensile strength of the sisal fiber reinforced concrete. The results indicated that the sisal fibers are effective in increasing the impact strength of concrete.